EFISIENSI PRODUKSI DAN INCOME OVER FEED COST USAHA TERNAK SAPI PO MELALUI PEMANFAATAN PAKAN MURBEI - Setiawan, Duta (JURNAL RISET AGRIBISNIS & PETERNAKAN, 2016)
Based  on  the  agricultural  production,  Indonesia  has  very  high  potential  to  increase  mulberry production  through  the implementation of adapted and liable technology. The  research was conducted to study the ability of mulberry leave meal addition concentrates on the performance of Ongole Grade. This experiment used a randomized block design, with 4 treatments and 4 blocks. Treatments consisted of P1 (native grass and concentrate feed in the form of mulberry leaves meal and concentrate complete), P2 (native grass and concentrate feed in the form of mulberry leaves meal and corn concentrate), P3 (native grass and concentrate feed in the form of mulberry leaves meal and rice bran concentrate), P4 (native grass and concentrate feed in the form of mulberry leaves meal and concentrate tapioca waste). The experiment was conducted for 4 months with the adaptation periods for 2 weeks. Parameters measured were feed consumption, daily body weight gain, feed efficiency, Income Over Feed Cost (IOFC), revenue cost ratio. The results showed that the mulberry leave meal addition on different concentrate did not significantly (P>0,05) affect daily body weight gain, feed consumption, feed efficiency and Income Over Feed Cost (IOFC), and revenue cost Ratio. It is concluded that based on the nutrient digestibility, mulberry leave meal concentrate can be combined with a single concentrate such as corn, cassava waste meal or complete concentrate. Kata kunci: Pakan murbei, sapi PO, Income Over Feed Cost (IOFC)